2016
DOI: 10.1039/c5cp06972f
|View full text |Cite
|
Sign up to set email alerts
|

Isosteric and fluorescent DNA base pair formed by 4-amino-phthalimide and 2,4-diaminopyrimidine: melting, structure, and THz polar solvation dynamics

Abstract: An artificial base pair in the center of a duplex DNA oligomer, formed by 2,4-diaminopyrimidine and fluorescent 4-aminophthalimide C-nucleosides, is characterized spectroscopically, with a view towards its use in femtosecond solvation dynamics. Quantum-chemical calculations predict H-bonding energy equivalent to A:T. UV-vis absorption spectra provide insight into local melting at the 4-aminophthalimide modification site. Increase of temperature to nearly the melting temperature of the duplex leads to better hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 36 publications
1
20
0
3
Order By: Relevance
“…4AP is approximately the size of a purine and should therefore be directly applicable as an isosteric DNA base surrogate . Theoretical calculations and NMR structures of dsDNA modified internally with C‐nucleoside 1 opposite 2,4‐aminopyrimidine (DAP) as C‐nucleoside 4 revealed that out of three possible H bonds between them, only two are actually formed . A more serious impediment to future use is the fact that a significant fraction of the duplexes forms only a single H bond between 4AP and DAP, and that the backbone structure adjacent to this artificial pair is distorted from native B‐DNA.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…4AP is approximately the size of a purine and should therefore be directly applicable as an isosteric DNA base surrogate . Theoretical calculations and NMR structures of dsDNA modified internally with C‐nucleoside 1 opposite 2,4‐aminopyrimidine (DAP) as C‐nucleoside 4 revealed that out of three possible H bonds between them, only two are actually formed . A more serious impediment to future use is the fact that a significant fraction of the duplexes forms only a single H bond between 4AP and DAP, and that the backbone structure adjacent to this artificial pair is distorted from native B‐DNA.…”
Section: Methodsmentioning
confidence: 99%
“…This is due to the syn conformation of 3 (as discussed below), which interferes with base pairing and inhibits proper stacking within the duplex. [21] Labels 01-26 for the nucleotides are given in Scheme 1a nd in the Supporting Information, together with further details.Inour previous work on the pairing properties of 1 and 4 in DNA1-4, [19] an additional imino proton signal was found that could only be assigned to ac entral A:Tb ase pair, thus indicating that two conformations coexist in that case.F or the current DNA2-4,w ef ind no evidence that asecond structure or conformation is hidden in the data. [17a] If this state is populated, the deactivation into the S 0 state occurs in aradiationless manner.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…[18] 4AP weist ungefähr die Grçße eines Purins auf und sollte daher als isosteres DNA-Basensurrogat direkt anwendbar sein. [19] Die Tatsache, dass ein deutlicher Te il der Duplexe nur eine H-Brücke zwischen 4AP und DAPb ildet und dass die Rückgratstruktur neben diesem artifiziellen Paar von der nativen B-DNAa bweicht, ist ein noch ernsteres Hindernis fürd ie Zukunft. [19] Die Tatsache, dass ein deutlicher Te il der Duplexe nur eine H-Brücke zwischen 4AP und DAPb ildet und dass die Rückgratstruktur neben diesem artifiziellen Paar von der nativen B-DNAa bweicht, ist ein noch ernsteres Hindernis fürd ie Zukunft.…”
unclassified